2000
DOI: 10.3390/50200127
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Thorpe Reaction of an α-Alkoxynitrile

Abstract: α-Alkoxynitrile 1 in the presence of tris(methylthio)methyllithium 2 at -78ºC gave the dimer 5 instead of the expected C 1 -elongated product 3. The formation of compound 5 is explained in terms of anion formation and self-condensation, a variant of the Thorpe reaction. Scrutinizing the 1 H NMR spectra revealed that the enamine tautomer 5b is predominant over the imine 5a in the solvents investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Examination of the spectral data revealed that the product was an oxygenated β-enaminonitrile (general structure 2 ) arising via a Thorpe condensation (see Table ) . The facile intermolecular dimerization of cyanomethyl aryl ethers at low temperature was surprising, as Thorpe condensations of alkyl nitriles require elevated temperatures and prolonged reaction times. , The literature provides few examples of the Thorpe condensation of cyanomethyl ethers, and these are primarily examples of undesired side products that were isolated in poor yield. , Recognizing that β-enaminonitriles 2 could function as a scaffold for the construction of highly functionalized cytosine derivatives, we subjected a range of α-aryloxyacetontriles to our reaction conditions (Table ). These condensations afford excellent yields for a wide range of aryl ethers, including sterically hindered cases such as ortho -substituted aryl ethers 1b , d − f .…”
mentioning
confidence: 99%
“…Examination of the spectral data revealed that the product was an oxygenated β-enaminonitrile (general structure 2 ) arising via a Thorpe condensation (see Table ) . The facile intermolecular dimerization of cyanomethyl aryl ethers at low temperature was surprising, as Thorpe condensations of alkyl nitriles require elevated temperatures and prolonged reaction times. , The literature provides few examples of the Thorpe condensation of cyanomethyl ethers, and these are primarily examples of undesired side products that were isolated in poor yield. , Recognizing that β-enaminonitriles 2 could function as a scaffold for the construction of highly functionalized cytosine derivatives, we subjected a range of α-aryloxyacetontriles to our reaction conditions (Table ). These condensations afford excellent yields for a wide range of aryl ethers, including sterically hindered cases such as ortho -substituted aryl ethers 1b , d − f .…”
mentioning
confidence: 99%